Dampak Pemberitaan Media Massa terhadap Kasus Korupsi yang Melibatkan Artis di Indonesia - Dinda Elissa Agustina; Nabilla Meymey Maulidina; Yeni Oktafiani Putri; Muhammad Rio Rizki Andra; Muzahid Akbar Hayat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Corruption remains a major issue in Indonesia, significantly affecting various sectors, including the entertainment industry. When public figures, particularly celebrities, become involved in corruption cases, it not only tarnishes their personal image but also shakes public trust in the entertainment industry and social institutions as a whole. This study aims to analyze how mass media covers corruption cases involving celebrities and the impact of such coverage on public perception. Using a qualitative research approach, the study examines news articles, television broadcasts, and online media publications about celebrity corruption cases over the past five years. The findings reveal that mass media plays a crucial role in shaping public opinion, either worsening or improving the public’s view of the individuals involved. Media emphasis on the sensational aspects of celebrity scandals often overshadows the larger issues of corruption in the political and governmental systems. This article concludes by highlighting the need for more responsible reporting that not only addresses the moral and personal aspects of the individuals involved but also educates the public on the broader implications of corruption in society.